Hubungan Pengetahuan dan Sikap Ibu Postpartum tentang Persalinan di Fasyankes dengan Pemilihan Pertolongan Persalinan - Ratu Kusuma (Jurnal Ilmiah Universitas Batanghari Jambi, 2018)
Safe childbirth is childbirth that helped by health personnel in health care facilities. Coverage of childbirth in health care facilities in Jambi province did not reach strategic plan target yet (77.00%), achievement (63.03%), Jambi city (93.86%) and the public health center did not reach target province yet (90%) that is the public health center Talang Bakung (79.00%) and Pal Merah II (78.00%). This study aimed to determine the correlation of knowledge and postpartum mothers attitude about childbirth in health care facilities with a selection of helping in childbirth at the public health center Talang Bakung. This is an analytic descriptive research; with total populations were 32 postpartum mothers, it used total sampling technique. Instrument test was conducted at the public health center Pal Merah II toward 10 postpartum mothers; an instrument used demographic data instrument, knowledge instrument, attitude instrument, and selection of helping in childbirth instrument, with fisher exact test and contingency coefficient. The findings indicated that there is no significant correlation between knowledge and attitudes of childbirth in healthcare facilities with a selection of helping in childbirth with each score p is (p=0.444 p=1.000), contingency coefficient (p=0.399, p=1.000). It is concluded that knowledge and attitude of the postpartum mother about childbirth in healthcare facilities did not affect in a selection of childbirth place chosen by the mother. For the next researcher to research about childbirth in healthcare facilities with the different method.